2015
DOI: 10.1093/jcr/ucv047
|View full text |Cite
|
Sign up to set email alerts
|

Navigating by the Stars: Investigating the Actual and Perceived Validity of Online User Ratings

Abstract: This research documents a substantial disconnect between the objective quality information that online user ratings actually convey and the extent to which consumers trust them as indicators of objective quality. Analyses of a data set covering 1272 products across 120 vertically differentiated product categories reveal that average user ratings (1) lack convergence with Consumer Reports scores, the most commonly used measure of objective quality in the consumer behavior literature, (2) are often based on insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
164
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 273 publications
(185 citation statements)
references
References 62 publications
12
164
0
Order By: Relevance
“…Experts' opinions, though, are not as ubiquitous as online reviews. Further, consumers relate more to the opinions of peers, rather than those of professionals – who are paid to write reviews (De Langhe et al ., 2016).…”
Section: Economic Dimensionmentioning
confidence: 99%
See 3 more Smart Citations
“…Experts' opinions, though, are not as ubiquitous as online reviews. Further, consumers relate more to the opinions of peers, rather than those of professionals – who are paid to write reviews (De Langhe et al ., 2016).…”
Section: Economic Dimensionmentioning
confidence: 99%
“…Alongside online reviews, Öğüt and Onur Taş (2012) included a more objective quality cue, that is, the number of stars assigned by national agencies to hotels. Using data from Booking, one of the most popular OTAs, the author found that an increase in valence (average rating) has a positive and statistically significant effect on hotel room sales (proxied by the number of reviews); the official star rating, instead, does not affect the hotel performance – providing support to studies showing that consumers do read official certification labels but eventually put more weight on peers' feedback (De Langhe et al ., 2016). The positive role of valence has also been established in other industries.…”
Section: Economic Dimensionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even in adulthood, we are often presented with mean values in newspapers or television adverts (e.g., comparing the miles per gallon of two car models or the battery life of two smartphones) and expected to decide whether there is a meaningful difference. Problematically, research suggests that we place more weight than we should on these types of average ratings (e.g., de Langhe, Fernbach, & Lichtenstein, 2016). Statistically, information about the means alone is insufficient for making such decisions.…”
Section: Introductionmentioning
confidence: 99%